Long term yield of rubber and timber in some promising Prang Besar clones in India - Mydin, Kavitha K.; John, Alice; Narayanan, C. (Journal of Plantation Crops, 2015)
Nine Prang Besar clones were evaluated in a large scale trial laid out in 1989 at the Central Experiment Station of the Rubber Research Institute of India. Rubber yield and its attributes including girth, girth increment rate under tapping, summer yield and secondary traits like incidence of pink disease and tapping panel dryness (TPD), were studied along with stability in long term yield in the clones in relation to the high yielding popular clone RRII 105. Long term yield over 14 years was highest in clones PB 280 (70.7 g tree-1 tap-1), PB 312 (70 g tree-1 tap-1) and PB 314 (68.8 g tree-1 tap-1) which were comparable and superior to rest of the clones. PB 311 was the second best yielding clone with 65.5 g tree-1 tap-1 over 14 years of tapping. This clone was the only promising yielder with stability in yield over the years. In terms of summer yield , the clone PB 280, recorded the best performance in all the three panels indicating its capability to produce more latex in the summer months too when the trees undergo stresses from refoliation as well as low moisture and high temperatures. The promising yielders from the present study, clones PB 280, PB 312 and PB 314 showed very low incidence of pink disease in the immature stage with only 1.5 to 1.7 per cent trees affected. The occurrence of TPD after 16 years of tapping was lowest in clone PB 280 (10.7%) and high in PB 314 (26.6 per cent). Estimates of genetic parameters revealed rubber yield and bole volume to be highly heritable traits. Correlations revealed yield per unit girth to have a close relationship with yield over 14 years and summer yield over 11 years. Clone PB 280 has proven to be a high yielding clone with very good secondary attributes like low incidence of pink disease and TPD. Clone PB 312 has proved its merit as a very promising latex timber clone. PB 314, among the best rubber yielding clones with a high yield per unit girth (0.8 g dry rubber cm-1 girth), though prone to TPD, has shown a low incidence of pink disease. The study indicates scope for further upgradation of clones PB 280, PB 312 and PB 314 in the planting recommendations for the traditional rubber growing regions of India.